Towards 2030. Enhancing 21st century skills through educational robotics - Gratani, Francesca; Giannandrea, Lorella (Frontiers in Education, 2022)
Recent technological advances require new learning and teaching methods and a reform of traditional school curricula to promote STEM and 21st-century skills. Educational robotics is considered a powerful tool, not only to learn programming, but also to enhance soft and transversal skills, such as problem-solving, metacognition, divergent thinking, creativity, and collaboration. This contribution presents a one-year research project aimed at integrating maker education and educational robotics into the primary and lower secondary school curriculum. The project is developed through a multidisciplinary and longitudinal approach and adopts the Design-Based Implementation Research methodology. It involved 50 fourth and fifth grade Italian students until the following school year. As an integrating background theme, we chose the 17 Goals outlined by the UN in the 2030 Agenda. Each selected goal was addressed by solving challenges in groups. Educational robotics became a tool for learning many concepts, such as renewable energies, human body systems or states of matter, but especially for working on creativity and ability to design, build, collaborate, and revise. We investigated students’ attitude towards STEM and 21st-century skills and their perceived school self-efficacy administrating two questionnaires pre and post the two parts of the project. This paper discusses findings on students’ attitude towards 21st-century skills. In the post analyses of both Part 1 and 2, this field showed the highest scores compared to STEM fields. The pre-post data show an improvement in organizational, interpersonal, and leadership skills from Part 1, but also a gradual increase in personal and management skills.